THE INFLUENCE OF INTENTION FINTECH USAGE ON ISLAMIC FINANCIAL INCLUSION IN INDONESIA WITH EXTENDED UTAUT THEORY - Abdul Aziz Idham; Rininta Nurrachmi; Wahyu Dwi Agung (Department Islamic Economics, 2026)
Despite the rapid growth of digital transactions in Indonesia, Islamic financial inclusion remains disproportionately low compared to the Muslim population size. There is a lack of comprehensive understanding regarding how religious values interact with modern technology acceptance models in the Shariah fintech landscape. Previous studies have extensively used UTAUT and UTAUT2 to measure general fintech adoption, but few have integrated